Antecedents of Electronic Word of Mouth (eWOM) Adoption in the Purchase of Cosmetics in Ecuador: Does Gender Moderate Relationships? - Madelyn Mendoza-Moreira; Beatriz Moliner-Velázquez; Gloria Berenguer-Contri; Irene Gil-Saura (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
Social networks have emerged as a powerful tool for communication and marketing, enabling two-way user participation and fostering a conducive environment for electronic word of mouth (eWOM). This study examines how social influence, eWOM engagement, and perceived eWOM credibility affect its adoption, while also exploring the moderating role of gender in these relationships. Using a sample of 371 cosmetics consumers in Ecuador, a causal model was estimated using the PLS method. The findings confirm that social influence significantly impacts eWOM engagement and credibility, contributing to its adoption. Additionally, gender moderates the relationship between informational influence and eWOM credibility. This study also highlights the need to replicate the model in different contexts and with more diverse samples to enhance the generalizability of the findings. By enriching Erkan and Evans’ IACM theoretical framework, this research extends the understanding of eWOM dynamics in the cosmetics sector. Moreover, it offers a comprehensive perspective on the eWOM adoption process by incorporating underexplored variables and providing empirical evidence from an understudied region, such as Latin America.